New insights into the biotransformation of weathered hydrocarbons in soil - Brassington, Kirsty J. (Cranfield University, 2008)
Weathered petroleum hydrocarbons are a highly complex, important soil contaminant. After forty years of petroleum research, weathered hydrocarbons are still not sufficiently understood or appropriately accounted for in contaminated land risk assessments or the associated analytical methods that inform them. Improved insights into these contaminants potential for biotransformation and their residual toxicity are essential for improving risk assessments, bioremediation strategies and effective regeneration of previously contaminated land. This thesis explores the biotransformation of weathered hydrocarbons in the context of risk assessment and management. The research includes a critical review and synthesis of six in-house historical pilot studies, implementation of a novel ultrasonic solvent extraction method for petroleum hydrocarbons and development of analytical tools, providing new insights for human and environmental risk assessments. The biotransformation potential and subsequent effect on the toxicity of two weathered hydrocarbon contaminated soils were investigated using soil microcosms. The use of a previously remediated soil provided novel insight into extended bioremediation potential for petroleum hydrocarbon residues to undergo further biotransformation. The novel ultrasonic extraction method developed collaboratively is a preferred alternative to traditional Soxhlet methods with very high precision (RSD ≤ 10%) and extraction efficiencies. Key benefits of the technique include reduced costs, shorter extraction times (1 h. vs. 8 h.) lower solvent consumption (40 ml vs. 150 ml) and improved extraction efficiencies (recovery ≥ 95 %). Ecotoxicological responses (using mustard seed germination and Microtox® assays) showed that a reduction in total petroleum hydrocarbon (TPH) load within soils could not necessarily be linked to a reduction in residual toxicity, thus reductions in TPH alone is not a suitable indicator of risk reduction. The residues in the previously remediated soil underwent further biotransformation with losses of up to 86 and 92 % in the aliphatic and aromatic fractions respectively. Grinding of this soil was shown to reduce the effectiveness of a nutrient treatment on the extent of biotransformation possible by up to 25% and 20% for the aliphatic and aromatic hydrocarbon fractions, respectively. Toxicity assays confirmed that biotransformation is not physically driven by surface area limitations, contrary to expectation, as responses of ground and un-ground soils were not significantly different (P>0.05). This may have implications for future studies using grinding as a pre-treatment, where biotransformation may be limited by grinding rather than other factors. Both the soils showed significant biotransformation (P<0.05) after 16 weeks of treatment. However, although the soil not previously treated had significantly less TPH losses, a loss of up to 92% shows that further degradation of this soil is possible even though previous investigations had suggested biotransformation had stopped. This has implications for bioremediation practitioners in that it questions whether bioremediation could be restarted and lower concentrations achieved, and warrants further investigation.